(untitled) (Mustansiria Dental Journal, 2023)
Background: The common microorganism in caries process are Streptococcus mutans and Lactobacilli. Candida albicans have correlation with Streptococcus mutans for enhanced dental caries. Cold Atmospheric Plasma (CAP) is called as non-thermal as result of electrons are more heated than heavy particles which are at room climate. CAP jets are ionized native gas outflow, produced underneath typical pressure through microwaves, high frequency or pulsed direct current employing noble gases. There are many application of CAP in dentistry: in periodontology, implantology, prosthodontic, operative dentistry and in cariology. This study aimed to measure the sensitivity of the S. mutans and C. albicans to CAP jet. Material and methods: In this experiment, newly developed Cold atmospheric plasma jet (Iraqi made) using argon gas at a Gas flow rate 10 l/min, 175volt and Frequency 2.45 GHz At room temperature such that the nozzle tip had a maximum distance of 2mm from the agar plate. Cold atmospheric plasma effect was tested at different times on the viable numbers of Streptococci mutans and Candida albicans. Result: Through the irradiation of CAP jet on agar plates the antimicrobial efficacy for S. mutans and C. albicans was measured at different time the 3, 6, 9 minutes. Multiple pairwise comparisons using Tukey HSD showed there is significant reduction of colony forming unit (CFU) for Streptococci mutans by plasma at all time compared to control. multiple pairwise comparisons using Tukey HSD showed there is highly significance differences for C. albicans was observed for all times in comparison to control (p<0.01). The data of the current study was analyzed using statistical package for social science (SPSS version 22). Thus, it can be concluded that Cold Atmospheric plasma (argon gas) jet have anti-microbial efficacy against Streptococci mutans and Candida albicans. but it effects on Candida albicans more than on Streptococci mutans.